Drug interactions between direct-acting oral anticoagulants and calcineurin inhibitors during solid organ transplantation: considerations for therapy. Issue 8 (3rd August 2019) - Lam, Edwin; Bashir, Babar; Chaballa, Mark; Kraft, Walter K.
ABSTRACT: Introduction : There is a high incidence of venous thromboembolism (VTE) in solid organ transplant recipients. The safety and efficacy of direct-acting oral anticoagulants (DOAC) have been well established in clinical practice for the prevention and treatment of VTE in broad populations. However, the management of VTE in the setting of solid organ transplantation remains a challenge to clinicians due to limited evidence of DOAC usage with calcineurin inhibitors. Areas covered : The current literature available on the pharmacokinetic–pharmacodynamic interaction between DOACs and calcineurin inhibitors is presented. A comprehensive review was undertaken using PubMed, Embase, drug product labeling, and drug product review conducted by the US Food and Drug Administration using Drugs@FDA. The potential for mitigation strategies and clinical management using extant knowledge is explored. Expert opinion : Immunosuppression therapy is necessary to prevent graft rejection by the host. The sparsity of data together with the lack of well-designed prospective studies of DOAC use in solid organ transplant recipients presents a unique challenge to clinicians in determining the clinical relevance of possible drug interactions. Existing evidence suggests that with attention to concomitant drug use and renal function, the co-administration of DOACs and calcineurin inhibitors is safe and effective.